Effects of repeated use of post-exercise infrared sauna on neuromuscular performance and muscle hypertrophy - Ahokas, E. K.; Hanstock, H. G.; Kyröläinen, H.; Ihalainen, J. K. (Frontiers in Sports and Active Living, 2025)
Purpose: The aim of this study was to investigate whether regular use of infrared sauna (IRS) after training can promote neuromuscular performance and positive changes in body composition during a 6-week training period.